2. Рівносильні рівняння:
2х+3х=10 та 5х=10
0х=3 та х+2=х+3
3. 3х+5=х+11; 2х=6; х=3
5(х-1)=2х (дальше не видно)
Пошаговое объяснение:
2х + 3х = 10 => 5х = 10
5х = 10 => 5х = 10
0 * х = 3 => х + 2 = х + 3
0х = 3 => 0х = 1
3х + 5 = х + 11
3х - х = 11 - 5
2х = 6
х = 6 : 2
х = 3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
2. Рівносильні рівняння:
2х+3х=10 та 5х=10
0х=3 та х+2=х+3
3. 3х+5=х+11; 2х=6; х=3
5(х-1)=2х (дальше не видно)
Пошаговое объяснение:
2х + 3х = 10 => 5х = 10
5х = 10 => 5х = 10
0 * х = 3 => х + 2 = х + 3
0х = 3 => 0х = 1
3х + 5 = х + 11
3х - х = 11 - 5
2х = 6
х = 6 : 2
х = 3